Optimized extraction of polysaccaride from Pseuderanthemun caruthersii (Seem.) Guill. . var. atropurpureum (Bull.) Fosb - Bac, Vo Hoai; Huong, Nguyen Thị Thanh; Truong, Le Van (Academia Journal of Biology, 2018)
Pseuderanthemum carruthersii (Seem.) Guill. var. atropurpureum (Bull.) Fosb is a tree native of Vietnam, this medicinal leaf has a high viscosity that has been used to heal wounds, heal the sores, stop bleeding... Polysaccharide has attracted great attentions for its benefits to human health. Polysaccharide from natural sources have diverse anti-inflammatory, anticoagulant and wound healing activities. Polysaccharide is not only valuable in medicine, also widely used in foodstuffs such as gel thickening or emulsifying agents, emulsifiers, fillers. The polysaccharide content in P. carruthersii var atropurpureum leaves was (11.63 ± 0.375)% in dry weight. The appropriate polysaccharide extraction conditions were determined: water, material/solvent ratio (1g/25ml), extracted temperature of 60°C, extraction time 15 hours. The polysaccharide composition was purified by TCA 10%, with a purity of (71.47 ± 0.94)%.